Pengaruh Minimasi Pajak, Mekanisme Bonus dan Exchange Rate terhadap Transfer Pricing dengan Komite Audit sebagai Variabel Moderasi - Hexana Sri Lastanti; Bella Nabilla Lukita Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Transfer pricing is a transaction of goods and services between several divisions in a business group at unreasonable prices, either by increasing or decreasing prices, mostly carried out by multinational companies that carry out cross-border activities. The aim, first, is to manipulate the amount of profit so that tax payments and dividend distributions are low. Second, inflating profits to polish financial reports. The country lost trillions of rupiah due to the transfer pricing practices of foreign companies in Indonesia. This research aims to obtain empirical evidence of the influence of Tax Minimization, Bonus Mechanisms, and Exchange Rates on Transfer Pricing. This research uses secondary data with a sample of mining companies for 2019-2022 on the IDX for 4 years. The result obtained is that Tax minimization variables have a significant effect on transfer pricing and the audit committee strengthens this effect, while the bonus mechanism and exchange rate have no effect on transfer pricing and the audit committee does not strengthen the effect.